Post-apocalypses, Imperial Dreams, and Neutrotopies: Visions of Hungary’s Future in Contemporary Science-Fiction Short Stories - Domokos, Áron (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2020)
There have been umpteen endeavours to define science fiction. Similarly, a number of slogans have been used to characterize the genre. According to one of them, science fiction is "today's warning for tomorrow". As a matter of fact, science fiction is in a state of flux, and it is "made by the interactions of various claims and practices by writers, producers, distributors, marketers, readers, fans, critics and other discursive agents” (Marc Bould-Sheryll Vint, cited by Rieder 2017). Nevertheless, it needs to be pointed out that the ominous reading of the slogan quoted above can still adequately describe almost all subgenres. The present paper takes a closer look at contemporary Hungarian short stories written in the science fiction tradition. More specifically, pieces published in 2013, 2014 and 2015 in the periodicals "Galaktika Magazin" and "Új Galaxis Magazin" as well as in the "Ad Astra” antologies will be examined. The aim of the study will be not only to present the various visions of the future of Hungary that we can encounter in the short stories in question, but a preliminary classification of the main similarities and differences of these visions will also suggest that some tendencies concerning contemporary social imagination can be established on the basis of the works under scrutiny.
Keywords: science-fiction • future-vision • Hungary • (post)apocalypse • neutrotopia